PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT YANG TINGGAL DI “RUSUNAWA” KELURAHAN BAYEM KECAMATAN KUTOARJO KABUPATEN PURWOREJO (STIE Rajawali Purworejo, 2021)
This study aims to examine the influence of price and quality of service on the satisfaction of people living in Rusunawa, Bayem Subdistrict, Kutoarjo District. The data collection technique in this research was obtained by observation, interviews, questionnaires, documentation and library studies. The population in this research is the people living in Rusunawa, Bayem Subdistrict, Kutoarjo District, numbering 54 families. The sampling technique used is a saturated sample, namely where all members are sampled. So the number of research samples is 54 families. Data collection methods are through observation, interviews, questionnaires, documentation and library studies. Data analysis techniques use multiple correlation analysis, multiple regression, tests and determination tests. The research results from multiple correlation analysis for the price variable obtained a value of 0.693 and for the service quality variable obtained a value of 0.679, so the relationship between the price variable and the service quality variable on public satisfaction is strong, because This figure is in the interval 0.60-0.799, which means it is strong. Multiple regression analysis produces the equation Y=3.320+0.501X1+0.329X2. The price variable has a coefficient of 0.501. The value of 0.501 means that if the value of the price variable increases by 1 unit and the other variable (service quality) is considered constant then the level of public satisfaction is 0.501. The service quality variable has a coefficient of 0.329. A value of 0.329 means that if the value of the service quality variable increases by 1 unit and the other variable (price) is considered constant then the level of public satisfaction is 0.329. Determination analysis produces an R Square figure of 0.526, this figure is called the coefficient of determination value. The determination value is 0.526 or 53%. This figure means that 53% of the level of community satisfaction can be explained using price and service quality variables. Meanwhile, the remaining 47% is likely influenced by other variables that were not studied, such as promotion and location. Hypothesis testing (t test) shows that between the price variable and consumer satisfaction there is a positive and significant influence so that H1 is accepted and H0 is rejected, then between the service quality variable and consumer satisfaction there is also a positive and significant influence so that H2 is accepted and H0 is rejected. The f test shows that the price variable and the service quality variable together have a positive and significant influence on consumer satisfaction so that H3 is accepted and H0 is rejected.